Maternidade e relação mãe-bebê no contexto do luto materno - Silva, Priscila Nassif da (Universidade do Vale do Rio dos Sinos, 2012)
This Master ́s Dissertation discusses motherhood and mother-infant relationship in the context of maternal grief. It consists of two papers, one theoretical and one empirical. The theoretical paper is a systematic review of the literature on maternal and child bereavement and subsequent to its execution, a search was conducted in national databases Scielo, Lilacs and BVS-Psi with keywords grieving mother, bereaved mother and mother and mourning. Was performed also a search in international databases Scopus, ScienceDirect and PubMed with the keywords Grieving mother, bereaved mother and mourning mother, comprising the period from 2000 to 2012. Of the total of 1953 found only 17 met the inclusion criteria. The results indicate that the relationship with his son addressed in subsequent studies is more international than in national studies. Furthermore, the number of international studies that addressed the pregnancy after loss is greater than those who investigated the relationship with the child after birth.The empirical study aimed at investigating how the mother experiences the new maternity after the loss of a child and understand how this experience may influence the relationship with the new baby in the first half of the first year of life the same. The participants were four adult women, aged between 20 and 38 years. They were mothers of newborns up to six months of age, with a history of previous loss of a child, regardless of age and elapsed time of loss. Were used as instruments of the Assessment Instrument Prolonged Grief Disorder (PG-13), semi-structured interviews about the grieving mother, and about the experience of motherhood and current relationship with the new baby, and the observation of mother-infant interaction. Each case was analyzed individually, seeking their particularities, and then compared to the others in order to investigate the similarities and differences between them. The results indicate that although mothers are still showing signs of mourning, three of them seem to constitute adequate link with subsequent children. Only one of participants seems to have enough trouble linking with his daughter.
Keywords: Luto materno; Filho subsequente; Maternidade; Relação mãe-bebê; Maternal mourning; Subsequent child; Maternity; Mother-infant relationship; ACCNPQ::Ciências Humanas::Psicologia